(untitled) (Research, Society and Development, 2021)
Difficulties with adequately teaching mathematics is a challenge not yet overcome by teachers. It is an important subject that directly involves educators and teachers, and indirectly society. New proposals for teaching mathematics have not been completely implemented and must be tested among the many levels of student life. One possibility for bringing teachers in accord with new teaching strategies is by pedagogical development, such as attending specific courses for teaching, to at least become aware of new methodologies and to learn how to apply them. The purpose of this work was to analyze the use of the Mathematical Modeling methodology in a course offered in a graduate Environmental Sciences curriculum using the active methodologies. The aim was to assess the development of cognitive abilities, favoring reflection and questioning into mathematical modeling, that occurred during remote teaching due to the pandemic. A structured questionnaire was given to students and the responses were used to interpretate their perception of the discipline/course and active methodology proposed. The problems cited by other authors, such as limited time and a culture engrained in traditional teaching, were observed by the present study, indicating the need in to introduce mathematical modeling and problem solving in the initial phases of teaching mathematics.